Manifestation of Dark Personality Behavior: Indigenous Study on Indonesian Workers - Putri, Rachmalia Wida; Nuzulia, Siti (Journal of Social and Industrial Psychology, 2023)
Machiavellianism is one of the traits incorporated in the dark triad personality. The portrayal of individuals with Machiavellianism is manipulative, prioritizing personal interests, to look down on others. Studies on the manifestations of Machiavellianism personality behavior in Indonesia have never been conducted, information about it is widely obtained from studies that take a sample of populations in countries that grow up in individualist cultures. While Indonesia itself is a country that grows in a collective culture with the habits of its people tend to depend on each other and prioritize their groups. Thus, the form of manifestation of Machiavellianism behavior in collective culture is thought to appear in line with collective values. This study aims to determine the manifestations of dark personality behavior of machiavellianism in Indonesian workers with a collective cultural background. In this study using an indigenous psychology approach with a quantitative descriptive research design. The application of quota sampling technique was used involving 760 respondents. The data collection tool used is a research instrument created by researchers and then analysis is carried out using percentage descriptive techniques and categorization. In this study, results were obtained such as: (1) positive and negative behavior of machiavellianism individuals in the work environment divided into self, interpersonal relationships, and performance; (2) the impact on personal and work relationships when dealing with Machiavellianism individuals in the work environment is divided into positive, negative, and neutral categories; (3) the least favorable behavior of Machiavellianism individuals in the work environment that gets the highest percentage is manipulative; and (4) how to deal with individual Machiavellianism in the work environment is divided into the categories of proactive, avoidant, learning, and managing emotions.